Detection of Cryptosporidium Infection in Domestic Pigeons in Baghdad City Using Conventional PCR Technique - ‪Yahya F. Hashim; Mohammed TH. S. Al Zubaidi (Iraqi Journal of Industrial Research)
Cryptosporidium infection poses a significant threat to domestic pigeon populations worldwide, Pigeons serve as vectors and may transmit the parasite to other avian species, therefore playing a significant role in zoonotic transmission. This study aimed to investigate the prevalence of Cryptosporidium spp. in domestic pigeons in Baghdad, Iraq, using conventional PCR and to assess the influence of age, sex, and seasonal variation on infection rates. During the study period of six months, from 1st October to end of March, 120 domestic pigeons were sampled, and fecal samples were collected for genetic analysis by using a conventional PCR. The overall infection rate was found to be 70.83%, with no significant difference between male and female pigeons, and infection rate of females was highest 82.98%. However, younger pigeons below 6 months of age exhibited a higher infection rate 78.26% compared to adults with significant differences. Seasonal variation was observed, with the highest infection rates recorded in February 95% and January 85%. According to molecular analysis the results confirmed the high presence of Cryptosporidium spp. between domestic pigeons in Baghdad city. In conclusion the study reported high prevalence of Cryptosporidium infection in domestic pigeons in Baghdad, Iraq, with significant age-related variations and seasonal fluctuations.